PENERAPAN MODEL KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 005 RANTAU PANJANG KIRI KEC.KUBU BABUSSALAM KAB.ROKAN HILIR - Rasniwati, Rasniwati; Daud, Damanhuri; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Science learning in class III SDN 005 Rantau Panjang Kiri is low an average grade 63,96 this is caused by the learning is done by texs oriented book, wearing a lecture (conventional) and exercises with student involvement was minimal and many students are passive while learning. This research aims to improve learning outcomes 005 Grade III SDN Rantau Panjang Kiri Academic Year 2014/2015 through